DINAMIKA BUDAYA LINGKUNGAN DALAM MENYIKAPI PERUBAHAN BUDAYA SOSIAL DI LINGKUNGAN 1 KEL. KEDAI DURIAN KEC. MEDAN JOHOR KOTA MEDAN - Nurjannah; Siti Fatinnah Nurjannah; Salsabila Br Ginting; Husna Nurhuda Lubis; Nabila; Fahira Cahaya Putri; Aldi Sulaiman H (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social cultural changes in the Community Environment 1 Kelurahan Kedai Durian, Medan Johor District, Medan City, have had a significant impact on the dynamics of environmental culture. This study aims to understand and address how social attitudes change in the Community and how they respond to social changes to maintain their social cultural identity. This Research Method uses a Qualitative method with Interview Techniques and direct observation by interviewing one of the Local Neighborhood Heads. The results of the study show that the Community Environment 1 Kelurahan Kedai Durian, Medan Johor District, Medan City, has an adaptive strategy in accepting and facing social cultural changes, such as accepting changes, accepting the impact of the Modern Era and maintaining positive cultural values. This study found that it is important to maintain and preserve local cultural attitudes and maintain the cultural identity of the Community.